The effect of infra low frequency–neurofeedback training on pistol shooting performance and attention in semi-skilled players - Bakhtafrooz, Safoura; Kavyani, Maryam; Farsi, Alireza; Alboghebeish, Saeed (Frontiers in Human Neuroscience, 2025)
PurposeNeurofeedback (NF) typically involves an operant conditioning or other reinforcement protocol aimed at self-regulating patterns of brain activation. Endogenous Neuromodulation, characterized by the absence of discrete reinforcers, has emerged over the last two decades with the extension of training into the infra-low frequency regime, i.e., below 0.1 Hz. Specifically, Infra-Low Frequency (ILF) Neurofeedback training has demonstrated efficacy in enhancing the self-organization and regulation of the central nervous system in considerable generality. The present study explores a pivotal question: Can Infra-Low Frequency (ILF) Neurofeedback, acknowledged for its influence on arousal, vigilance, and emotional states, effectively enhance both attention generally and shooting performance specifically? Additionally, we explored whether the training exerted beneficial effects on three attentional networks—Conflict, Orienting, and Alerting.MethodsTo assess shooting performance, we employed the Shooter’s Coordination Analysis Target Training (SCATT), while attention networks were gauged through the Attention Network Test (ANT). Twenty semi-skilled pistol shooters, aged 28–40, underwent both the ANT and SCATT assessments before and after completing 20 half-hour ILF-Neurofeedback sessions. The participants were randomly assigned to two groups: an ILF NFB group, which underwent 20 sessions of ILF NFB training, and a control group that received no NFB.ResultsOur findings revealed that ILF-Neurofeedback significantly enhanced performance. In the ANT, the training led to a reduction in Conflict and an increase in Orienting and Alerting.ConclusionThe study demonstrates the effectiveness of ILF-Neurofeedback in improving shooting performance, and in positively impacting all three attention networks assessed by the ANT.